The Effectiveness of Hand Exercise on Limb Function in Patient Coronary Artery Disease Posttransradial Artery Catheterization: Systematic Review - Herdiana, Dian; Herawati, Tuti; Yona, Sri (Indonesian Journal of Global Health Research, 2024)
Coronary Artery Disease (CAD) is leading cause of mortality worldwide. Catheterization using the transradial arterial (TRA) technique has been able to reduce morbidity and mortality rates from CAD, but this procedure also contributes to the occurrence of complications. The aim of this study was to search literature and analyse articles discussing the use of hand exercise on improving limb function in patients posttransradial cardiac catheterization. Methods: The design used was a systematic review with PRISMA adaptation. Articles were searched using databases: ScienceDirect, ProQuest, PubMed, Scopus and Hand Searching in Google Scholar. The keywords of article search were using “Coronary artery disease” AND “transradial artery catheterization” OR “Trans cardiac Catheterization” AND “hand exercise” AND “limb function. In the initial stage of information search on 5 October 2023, the total number of articles obtained before selection was carried out based on inclusion and exclusion criteria was 7273 articles. From the five databases used, selection was then carried out according to the inclusion and exclusion criteria. The inclusion criteria were research articles published in the last 10 years (2013-2023); use English; a journal article and open access; Involves adult respondents and full text articles. Exclusion criteria were encyclopedia articles, book chapters, conferences, correspondence, editorials, news, practice guidelines, protocols, systematic reviews, literature reviews and meta analysis. The results are discussing 7 articles published from 2013-2023. Conclusions Hand exercises are useful for restoring limb function within two hours after the procedure and over a long period of time.